Long-Term Effects of Maternal Smoking on Quality of Life. Results from the Copenhagen Perinatal Birth Cohort 1959–61 - SØren Ventegodt; Joav Merrick (The Scientific World Journal)
The Copenhagen Perinatal Birth Cohort 1959–61 is a prospective longitudinal perinatal study that included all deliveries (over 20 weeks gestation, birthweight over 250 g) that took place at the University Hospital (Rigshospitalet) in Copenhagen, Denmark during the period of September 21, 1959 to December 21, 1961 and used in this follow-up study to investigate the connection between maternal smoking during pregnancy and the quality of life of the child 31 to 33 years later. The latest follow-up study from the cohort was performed in 1993 and 7,222 of the surviving children were identified (now aged between 31 and 33 years) and contacted with a nonanonymous questionnaire on several aspects of quality of life issues.There were 4,626 usable responses (f = 2,489, m = 2,131) corresponding to a response rate of 64.1%. The children whose mothers were nonsmokers or smoked less than three cigarettes a day had a quality of life that was 2.7% better than those children whose mothers had smoked over ten cigarettes per day. At first glance these figures seem small; however, when compared with other early life factors we see that mothers smoking more than ten cigarettes per day is one of the most important early predictors in our study for the quality of life (QOL) of the child as an adult. As most people in our study have a QOL rating between 55% and 85%, 2.7% is about 10% of normal variation. It seems that exposure to tobacco smoke during pregnancy has a small but significant effect on the quality of life in later adult life. However, the underlying causal factor for this reduction in quality of life remains unclear. Nevertheless, pregnant mothers should be made aware of the potential long-term effects smoking can have on their children.